KEGIATAN INTELEKTUAL DI KESULTANAN PALEMBANG DARUSSALAM (1659-1823 M) - Choirun Niswah; Dodi Irawan; Choiriyah Choiriyah (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2022)
Writing this article aims to obtain information related to intellectual activities during the Palembang Darussalam Sultanate. The research method used is descriptive and qualitative analysis with a historical approach, namely by collecting library data from various written sources.This study aims to obtain information related to Islamic intellectual activity during the Palembang Darussalam Sultanate so that the discussion is carried out qualitatively or using textual descriptions. Writing and searching for data are obtained through documents, especially documents written in the form of scientific papers. These sources can be accessed in various ways such as through libraries and online media.The results showed that the palace or palace had a big role in intellectual activities during the Palembang Darussalam Sultanate. This is because the ruler or the Sultan provided extraordinary facilities and patronage to the ulama, so that scholars, writers, and poets emerged whose works are still read and taught by the people of the archipelago to this day, such as the two magnum opus works of al-Palimbani, Sair as-Salikin, and Hidayat. al-Salikin, the knowledge, and thoughts that had grown up in the Palembang Darussalam Sultanate as well as those that had grown in Aceh in the previous century, still carry the characteristics that marked the minds of the Islamic world in general at that time. However, knowledge and thoughts passed down in the past are very valuable for the future of Islam, especially in the present century due to advances in science and technology, humans are increasingly aware of their need for spiritual wealth, in which the past world is superior to our present world.